Toward Improved Environmental Stability of Polymer:Fullerene and Polymer:Nonfullerene Organic Solar Cells: A Common Energetic Origin of Light- and Oxygen-Induced Degradation - James Durrant (ACS Energy Letters, 2019)
With the emergence of nonfullerene electron acceptors resulting in further breakthroughs in the performance of organic solar cells, there is now an urgent need to understand their degradation mechanisms in order to improve their intrinsic stability through better material design. In this study, we present quantitative evidence for a common root cause of light-induced degradation of polymer:nonfullerene and polymer:fullerene organic solar cells in air, namely, a fast photo-oxidation process of the photoactive materials mediated by the formation of superoxide radical ions, whose yield is found to be strongly controlled by the lowest unoccupied molecular orbital (LUMO) levels of the electron acceptors used. Our results elucidate the general relevance of this degradation mechanism to both polymer:fullerene and polymer:nonfullerene blends and highlight the necessity of designing electron acceptor materials with sufficient electron affinities to overcome this challenge, thereby paving the way toward achieving long-term solar cell stability with minimal device encapsulation.